A preliminary assessment on magnitude of oral health problems among five selected primary care clinics of Malaysia and Myanmar in 2012 - Tin, Myo Han; Md Aris, Mohd Aznan; Sulong, Robiatu Adawiah (2013)
Background: There is growing evidence that oral health is related to local and systemic diseases by sharing common risk factors. Although, oral health has long been overlooked in the medical community, electronic medical records study in 2011 found that 1.2% of all encounters of the University Primary Care Clinic were oral diseases. The first point of contact for patients with Primary Care Physicians (PCPs) can facilitate preventive dental care through timely referrals to dental profession4. Objectives: To assess the oral health concern of general/family medicine practices which may be used to set primary and emergency oral health care training for primary care physicians Methods: A uniform structured format was used to collect total number of patients and the patients with oral health problems (OHPs) who attended at the selected 3 primary care clinics of Kuantan, Malaysia (a private, a public and a University clinic) and two private clinics of Myanmar (one from Yangon (City) and one from Hninthada District within 1st April, 2012 to 31st July 2012. A cross-analysis was done between demographic data, reason for encounter (RFE) and the countries under study. Findings: In Malaysia, range of proportion of oral health problem (OHP) per month among the 3 primary care clinics was from 4.2 to 25.7 per 1000 patients/month. That of two Myanmar private clinics was from 3.6 to 11.6 per 1000 patients/month. Although, age group differences- the younger age group more in Malaysia and the older age group more in Myanmar was seen, there was no gender differences. Although the common OHP in both countries were more or less same -dental caries, periodontal diseases, oral ulcer, hand-foot mouth disease (HFMD); and co-morbidity with medical diseases were more in Myanmar than in Malaysia. Discussion and conclusion: This study confirms that Oral Health Problem is an important health issue in reason for encounter of primary care practices. It is recommend that all primary care physicians be more aware of oral health problems and if necessary be made part of the training as a primary care physician.